دراسة فعالية أجهزة الترشيح بالتناضح العكسي( R.O ) وتأثيرها في جودة مياه الشرب - دباليز, عمار; قصير, أحمد; شحادة, مازن (Latakia University Journal -Engineering Sciences Series, 2019)
جاءت هذه الدراسة العلمية بعد الانتشار الكبير لأجهزة الفلترة المنزلية العاملة بتقنية التناضح العكسي في الأسواق من قبل الشركات المستوردة لها و وصولها إلى منازل المواطنين عبر مندوبيها الذين يحاولون صناعة رأي عام يشكك في سلامة المياه التي تقدمها الدولة وأمنها. قمنا بتطبيق منهجية علمية دقيقة للوقوف على حقيقـــة هذا الأمر و التحقق منه, و تم دراســة بعض من هذه الفلاتر, و أجرينا تقييماً للمياه قبلها و بعدها وفقاً لأهم المؤشرات الكيميائية و الجرثومية لمياه الشرب, و بالنتيجة تم التوصل إلى حقيقة أن المياه قبل هذه الفلاتر مطابقة للمواصفات القياسية السورية من الناحية الكيميائية و الجرثومية, أما بعدها فلوحظ انخفاض كبير في نسب الأملاح المنحلة, و تبين أيضاً بعد دراسة أخرى للنوعين (A, B ) فقط, أن أغشية هذه الفلاتر كانت عرضة للهجوم الجرثومي و ذلك بعد أن تم استعمالها لفترة تجاوزت خمسة الأشهر. الخلاصة الأهم هي أن المياه المقدمة من قبل الدولة لمنازل المواطنين هي مياه آمنة من الناحية الكيميائية و الجرثومية, و ندحض أي ادعاء مخالف لذلك بهدف التسويق و الترويج لشراء مثل هذه الأجهزة. Studying design parameters of oxidation ditches was done to achieve the best removal efficiency of organic pollutants, suspended solids, and nutrition elements (Nitrogen and Phosphorous) using a pilot at Wastewater treatment plant in AL-HARAH village– LATTAKIA City. The experiments were done in 2011. The pilot was operated with different hydraulic retention times from 8h to 32 h, F/M (0.033 – 0.132), MLSS( 2000 – 3800 ) mg/l, TC0 ( 9.3 – 26.5 ), pH( 7.5 – 8.44 ), dissolved oxygen in basin and after the end of aeration ( 0.4–6.9 ) mg/l, and returned activated sludge was 100%, the solids retention time in the pilot is ( 20-29 ) d. At every hydraulic retention time DO, pH, TC0 were determined in basin, and the input and output of BOD5, COD, TSS, TN, TP. The characterization of input wastewater to the plant treatment was determined, the average of BOD5in in Winter was 149 mg/l, and the average in Summer was 387 mg/l. The average of TNin and TPin during the studying period were 10.75 mg/l and 8.6 mg/l consecutively. The suitable hydraulic retention time is (14) h in Winter, and ( 18 – 24 )h in Summer. The percentage removal of BOD5 , COD, TSS, TP at hydraulic retention time = 24h was 91.4%, 91.25%, 92.34%, 18.91% consecutively, and denitrification did not carry out, and DO was2.5mg/l, and T C0=25.5, F/M = 0.09, pH=7.63. Denitrification and Phosphorous removal were 59% and 37.8% consecutively with anoxic zone in dynamic operating. Production sludge had good characters with thickening time 45 min, specific resistance parameter on filtration 362.8*1010 cm/g, and SVI=42.37 ml/g.